Preoperative status and in-hospital complications of coronary artery surgery in patients with pre-diabetes and type 2 diabetes mellitus. (25th November 2020) - Bezdenezhnykh, N; Bezdenezhnykh, A; Sumin, A; Barbarash, O; Kuzmina, A; Gruzdeva, O
Abstract: Aim: To assess the preoperative status and the rate of in-hospital complications of coronary artery surgery (CABG) in patients with pre-diabetes compared to patients with type 2 diabetes mellitus (type 2 DM) and normoglycemia. Materials and methods: 708 consecutive patients who underwent CABG between 2011 to 2012 were included in the study. All patients without positive history of diabetes underwent an oral glucose tolerance test (OGTT). The lab findings were interpreted in accordance with the recommended diagnostic criteria for diabetes and other glycemic disorders. Results: DM screening before coronary artery bypass grafting allowed to diagnose type 2 diabetes in 8.9% (n=63) and prediabetes in 10.4% (n=74) of the study population. The preoperative screening increased the number of patients with DM from 15.2% (n=108) to 24.1% (n=171), and with prediabetes from 3.0% (n=21) to 13.4% (n=95). The total number of patients with carbohydrate metabolism disorders increased from 18.2% (n=129) to 37.5% (n=266). All patients were enrolled into 3 groups based on their glycemic status: Group 1 - without carbohydrate metabolism disorders (n=442), Group 2 - pre-diabetes (n=95), Group 3 - type 2 DM (n=171). The analysis of in-hospital complications reported that patients with pre-diabetes more often underwent urgent peripheral artery bypass compared to the other two groups (p1–2=0.002 vs. p1–3=0.023). The highest rate of wound complications was found in patients with pre-diabetes (p1–2=0.012). In addition, a clear trend towards the rate of other in-hospital complications of CABG in the groups with pre-diabetes and diabetes was found. The regression analysis shows that type 2 DM was associated with the total number of significant complications (odds ratio (OR) 1.731, 95% confidence interval (CI) 1.131–2.626, p=0.012), prolonged in-hospital stay (OR 2.2229, 95% CI 1.412- 3.519, p<0.001), the risk of urgent peripheral artery bypass (OR 1.638, 95% CI 1.009–15.213, p=0.020), multiple organ dysfunction syndrome (OR 2.911, 95% CI 1.072–7.901, p=0.039) and the need for hemostasis correction using the extracorporeal methods (OR 3.472, 95% CI 1.042–11.556, p=0.044). All the associations described above remained significant when pre-diabetes was introduced into the regression model and any carbohydrate metabolism disorder was considered as a potential predictor of in-hospital complications. Additionally, an association between pre-diabetes and diabetes and the risk of acute renal damage (OR 1.700, 95% CI 1.067–2.612, p=0.024) and wound complications (OR 1.547, 95% CI 1.073–2.231, p=0.019) was observed. Conclusion: Pre-diabetes affects the in-hospital outcomes after CABG as well as diabetes mellitus. Our findings emphasizes the relevance of active preoperative detection of carbohydrate metabolism disorders. Funding Acknowledgement: Type of funding source: None